Making lCT Based Child Society by Collaborative Learning with SLMS: Ideas for Bangladeshi Primary School Leaders - Shanta Akther Sheema (JOURNAL OF EDUCATION, 2012)
LMS is a well known teaching method of ICT in the world. As in many other countries, it is not familiar in Bangladesh. However, to make the country a "Digital Bangladesh ", it is necessary to introduce ICT by LMS from primary education. Primary education is the basic of all education systems, so if all the primary school children learn to use ICT in their learning, they will be able to make knowledge based society infuture. For Bangladesh, with nearly 15 million people (Cencus  Report:2011), it is hard to make ICT access in primary education. At the moment only a small number of university students get  this access. In this situation the researcher wants to give some ideas and recommendations for the primary school leaders of Bangladesh which are obtained from  an Indonesian school, SD Muhammadiyah Condongcatur. The researcher used participatory observation and interview methodfor this idea. By using this idea from SD Muhammadiyah Condongcatur, the researcher wants to give a new ideafor making an ICT- based child society in Bangladesh by simple learning management systems (SLMS). Keywords: primary school leaders, ICT- based child society, SLMS